International democracy promotion and democratization in the Middle East and North Africa. Issue 1 (2nd January 2018) - Abbott, Lucy M.
ABSTRACT: This article offers an overview of the literature on international democracy promotion in relation to the Middle East and North Africa (MENA). It draws on the criteria of process tracing to evaluate the mechanisms, processes and episodes of democratization associated with international democracy promotion in the region. It finds that the literature lacks a clear account of how international democracy promotion relates to conditions for democratization and could pay greater attention to the role of media in either supporting or counteracting democracy promotion activities which impact democratization processes in the region.